Diego of the dead 2 [videorecording (DVD)] (FamilyEntertainment.tv, 2024)
It's The Day Of The Dead and Diego, the cutest skeleton in the underworld launches a comedy contest just in time for the Dia De Muertos festivities! Join us for an underworld adventure like no other, it's Diego Of The Dead 2!